Tourism inside Gated: The Transformation of Gated Housing in Peri-Urban of Bandung - Samsirina, Samsirina; Pratiwi, Wiwik Dwi; Harun, Ismet Belgawan (ASEAN Journal on Hospitality and Tourism, 2017)
Despite some physical similarities with the typology of gated housings developing in Metropolitan of Jakarta, there is uniqueness in gated housings growing in Bandung, especially in its peri-urban area. The uniqueness is the development of tourism activities inside those gated housing. A number of luxury residential complexes with gated characteristics in the peri-urban areas of Bandung have transformed into tourism areas. This phenomenon is interesting to study given the contrasted characteristics between gated housing and tourism. this paper discusses a number of case studies on tourism activities and facilities developing inside gated housings in peri-urban of Bandung. The research method used qualitative descriptive analysis and typo-morphology analysis. The study results have shown a number of unique typo-morphology of tourism facilities inside gated housings in the peri-urban area of Bandung as well as a number of their physical and operational characteristics differences from other tourism facilities in general. Gated housing itself is closely related to segregation. The results of this study have also indicated that the presence of tourism activities in gated housings as well as a number of local creative strategies applied by the management of the tourism facilities could become one of the solutions to minimize the extent of segregation posed by the gated housings and to improve the physical quality of the gated housing where the tourism facilities are located.Keywords: gated housing; peri-urban of Bandung; typology; transformation; tourism